Factors associated with poor prognosis in elderly biopsy-only glioblastoma patients - Edriss, Jana; Cheung, Julie; Kronvall, Erik; Nittby Redebrandt, Henrietta; Uvelius, Erik (Acta Neurochirurgica, 2025)
Purpose: Glioblastoma (GBM) in elderly patients has a poor prognosis. About one-third of patients have impaired perioperative performance status (PS) and often excluded from clinical trials. Brain biopsy is the standard diagnostic approach when resection is not feasible. Previous studies on preoperative prognostic factors have mostly focused on resected patients. This study aimed to identify preoperative factors associated with reduced three-month survival and treatment incompletion in elderly biopsy-only patients, with the three-month endpoint reflecting early mortality and rapid disease progression that often prevents treatment completion. Methods: We retrospectively reviewed biopsy-only GBM patients aged > 65 years between 2017 and 2020. Preoperative prognostic factors were analyzed using logistic regression, and overall survival (OS) was estimated using Kaplan–Meier. Results: A total of 132 patients were included. Median OS was 4.6 months, and 50% completed treatment. Palliative treatment was given to 17% of patients (median OS 1.3 months). Poor PS (OR = 0.2), larger tumor volume (OR = 0.9), and central tumor location (OR = 0.3) were independently associated with reduced three-month survival. Poor PS was the only predictor of treatment incompletion (OR = 0.06); in this subgroup, The median OS was 1.6 months, with only one of 21 completing treatment. Conclusion: In elderly patients with biopsy-only GBM, poor preoperative PS, central tumor location, and larger tumor volume were significantly associated with reduced short-term survival. Patients with poor preoperative PS were also less likely to complete treatment. These findings may aid in counseling on the potential benefits of biopsy in this vulnerable group.
Publisher Copyright: © The Author(s) 2025.
Keywords: Biopsy; Brain tumor; Elderly; Glioblastoma; Oncology treatment; Palliative care